The Specific Features Of Phrase Translation Based On American Short Stories (Texas Journal of Philology, Culture and History, 2025)
This article explores the specific features of phrase translation based on American short stories, with a focus on idiomatic expressions, collocations, and culturally embedded phrases. The study highlights the challenges faced by translators when dealing with phrases that do not have direct equivalents in the target language, particularly in the context of Uzbek. It discusses the importance of understanding both linguistic structure and cultural context in order to convey the original meaning and emotional tone of the source text. Various translation strategies—such as literal translation, adaptation, substitution, and explanatory translation—are examined to illustrate how phrase meaning and stylistic effect can be preserved. The research emphasizes that successful phrase translation requires not only linguistic proficiency but also deep cultural awareness and creative problem-solving skills